A moda francesa e as roupas íntimas: seu papel libertador feminino - Pagnan, Andreia Salvan (2012)
The female clothing used in the French court in mid-seventeenth century had a wealth of colors, textures and patterns that pass from that time to be decisive worldwide. Such influences bequeathed to the establishment of fashion as a form of change and achievement of man in society. Baroque influences were seen in the arts, literature, and also in an elaborate fashion with lace, ribbons and embroidery. The female used underwear at that time depicts the secondary role of women in society, repressed by the corset. An evolutionary analysis of intimate fashion since the French court of King Louis XIV discusses his role in liberating women's suppression.